Workers’ Perceptions of Social Security, Social Opportunities and The Challenges in Hotel Employment - Ganiyu, Rasaq Omokeji; Alatise, Remi Kasali; Kazeem, Kolawole Lateef (My University, 2024)
The study delved into the concept of social security as a fundamental human right, emphasizing its relevance in the hospitality industry, which contributes significantly to the global economy. Despite its substantial impact, the sector faces challenges, particularly in the form of precarious work. In order to gain empirical insights into this problematic, we took a comprehensive approach, engaging with 120 individuals from a dozen threestar hotels in Abuja, the Federal Capital Territory. To ensure consistency, we adhered to the European Hotelstars Union's classification criteria. Through thoughtfully crafted questionnaires, we delved into workers' perspectives on social security, social opportunities, and challenges. Employing both quantitative and qualitative methods, our analysis utilized frequency and simple percentage techniques, yielding 114 completed responses. The study unfolded the notion of social security as a fundamental human right, spotlighting its pivotal role in the vibrant hospitality industry, a cornerstone of the global economy. However, despite the industry's undeniable impact, the study reveals that hotel workers continue to grapple with social security and employment-related challenges that include human rights abuses, precarious working conditions, imposition of restrictive dress codes and gender-based violence. Based on findings, the study recommends the implementation of liberal dress codes among workers, provision of regular counseling and training, involvement of workers in the decision-making process, offering worker-friendly packages, and organizing relevant training programs to enhance staff skills and well-being, thus promoting sustainable development in the hospitality industry.
Keywords: Tourism; Hotel; Social Security; Opportunities; Challenges; Sustainable development